Disaster impacts on co-management networks: longitudinal and comparative analysis of Chilean small-scale fisheries - Marín, Andrés; Bodin, Örjan; Gelcich, Stefan; Castilla, Juan Carlos (Frontiers in Marine Science, 2023)
Fisheries co-management is a particular form of governance that is highly reliant on complex multi-stakeholder participation, collaboration and learning networks. Recent studies have highlighted its relational nature and investigated which kinds of social network structures define and enhance co-management possibilities to perform, adapt and deal with uncertainty and change. However, there is less understanding about the impacts of disasters and abrupt perturbations on co-management networks. In this research, we present a social network analysis of the impacts of the 2010 tsunami on co-management in the Chilean small-scale coastal benthic fishery. Based on data collected in 21 fisher organizations in the Bio-Bío region, heavily impacted by the tsunami, we assess whether and how co-management facilitating social relationships have changed after the event, as compared to 16 non-impacted organizations in the Valparaíso region. Baseline data (i.e., 2008) from both regions allows for before-after longitudinal analysis. We specifically look at changes in relational patterns between fisher organizations and multi-sector fishery counterparts (e.g., associated with post-disaster fishery and livelihood recovery needs). Our findings show that after the tsunami, co-management networks in Bio-Bío present reduced fragmentation and higher levels of perceived trust among actors in comparison to the non-affected region. A slightly lower tendency towards decentralization was also observed. These findings suggest that post-disaster adjustments have occurred among the same network actors. Co-management networks were flexible enough to be rewired as a consequence of abrupt perturbations triggered by the tsunami. Attention to changing governance networks can help identify key leverage points to support, taking advantage of and integrating post-disaster emerging relationships in decision-making processes and to secure equitable access to key resources and information.